The genetics underlying metabolic signatures in a brown rice diversity panel and their vital role in human nutrition - Brotman, Yariv; Llorente-Wiegand, Cindy; Oyong, Glenn; Badoni, Saurabh; Misra, Gopal; Anacleto, Roslen; Parween, Sabiha; Pasion, Erstelle; Tiozon, Rhowell N.; Anonuevo, Joanne J.; deGuzman, Maria K.; Alseekh, Saleh; et al. (Wiley, 2021)
Brown rice (Oryza sativa) possesses various nutritionally dense bioactive phytochemicals exhibiting a wide range of antioxidant, anti‐cancer, and anti‐diabetic properties known to promote various human health benefits. However, despite the wide claims made about the importance of brown rice for human nutrition the underlying metabolic diversity has not been systematically explored. Non‐targeted metabolite profiling of developing and mature seeds of a diverse genetic panel of 320 rice cultivars allowed quantification of 117 metabolites. The metabolite genome‐wide association study (mGWAS) detected genetic variants influencing diverse metabolic targets in developing and mature seeds. We further interlinked genetic variants on chromosome 7 (6.06–6.43 Mb region) with complex epistatic genetic interactions impacting multi‐dimensional nutritional targets, including complex carbohydrate starch quality, the glycemic index, antioxidant catechin, and rice grain color. Through this nutrigenomics approach rare gene bank accessions possessing genetic variants in bHLH and IPT5 genes were identified through haplotype enrichment. These variants were associated with a low glycemic index, higher catechin levels, elevated total flavonoid contents, and heightened antioxidant activity in the whole grain with elevated anti‐cancer properties being confirmed in cancer cell lines. This multi‐disciplinary nutrigenomics approach thus allowed us to discover the genetic basis of human health‐conferring diversity in the metabolome of brown rice.